Analyzing Educational Needs for PMRI-Based Instructional Videos: Addressing Fraction Division Challenges in Elementary Mathematics - Susanto, Edi; Susanti, Retno; Somakim, Somakim (Papanda Publisher, 2025)
This study investigates the needs of fifth-grade teachers and students at SDN 1 Dawas, Musi Banyuasin Regency, regarding the development of PMRI-based (Indonesian Realistic Mathematics Education) instructional videos for fraction division material. Employing a qualitative descriptive approach with needs analysis methodology, data were collected from five teachers and 29 students through in-depth interviews, classroom observations, and structured questionnaires. Data analysis followed systematic thematic analysis procedures including data reduction, display, and conclusion drawing, with validity ensured through triangulation. Results revealed that despite adequate infrastructure (93.79% resource availability, 89.66% internet access) and high student motivation (93.79% learning interest), significant gaps persisted in content mastery (60.69%), concept comprehension (65.52%), and problem-solving skills (54.48%). Teachers demonstrated moderate pedagogical competence (74% average) and recognized innovative media value (72%), yet faced implementation challenges with current materials meeting only 64% of needs. Notably, 92% student interest in technology applications remained underutilized. These findings indicate critical necessity for PMRI-based video development that contextualizes fraction division within students' lived experiences, accompanied by teacher professional development in pedagogical orchestration. The study contributes empirical evidence for PMRI implementation in rural Indonesian contexts, emphasizing that technological readiness requires corresponding pedagogical transformation and contextually responsive learning materials to bridge existing instructional gaps.